Max(imum) vegan : a case study on vegan products in the food service sector - Marcopoulos, Julia (SLU/Dept. of Economics, 2017)
Animal based foods have been important components of the Swedish diet for many years. As the meat, dairy and eggs require more resources than plants the sustainability advantage of the vegan diet is becoming incresingly acknowledged. However, research has shown evidence of it being difficult to change peoples’ dietry habits. This is especially true if the people are asked to give up on foods they value highly, such as meat. Max Hamburgerrestauranger AB is a Swedish food service company that realised that their own environmental footprint largely originated in the meat in their meals. In order to adress this problem they decided to launch five new vegetarian/vegan meals in the beginning of 2016. The campaign was a success and as a next step towards more sustainable business they are targeting to increase their number of vegan meals. The focus of this study is on the developments of vegan food in the food service sector. A shift from animal based diets to food that contain more vegan sources can be of importance in the context of sustainable development. Therefore, the aim of this study is to investigate hinders and opportunities for development of vegan fast food in the Swedish food service sector from a marketing perspective. The thesis is conducted using a qualitative research approach and the design is case study. Semi-structured interviews with key respondents have been used to collect data. This study identifies several hinders towards development of vegan fast food products. One is the state of meatnorm in society – that consuming meat is norm an consuming vegetarian/vegan is considered non-mainstream. Another is peoples’ wish to belong in a group, and therefore being afraid of stepping outside of the group when consuming vegan. The percieved worse taste of vegan fast food products compared to animal based equivalents was another hinder. Lastly the current political structures are viewed as hindering the development of vegan fast food products. Numerous opportunities were also identified. The sustainability, health and animal welfare advantages of vegan food are evident and could thusly be elivated more. There is a vego trend, or even shift towards vego being more common, occuring in Sweden today. Companies such as Max Hamburgerrestauranger AB can benefit from riding on the wave of change, and they in turn can have a key role in shaping the food of the future. The younger generation is according to the respondents positive towards veganism and this creates and opportunity. Making products that feel familiar to the consumers can be advantageous as that makes it easier for the consumers to percieve them as necessary. Lastly, communicating the vegan fast products in a positive way can create an opportunity for their further development.